PERENCANAAN PEMBUATAN TURN PAD AREA DI UJUNG RUNWAY 30 DI BANDAR UDARA DEPATI PARBO KERINCI - Reza Aldama; Siti Fatimah; Linda Winiasri (Prosiding SNITP (Seminar Nasional Inovasi Teknologi Penerbangan))
Depati Parbo Airport is an airport located in Hiang Village, Sireview Laut District, Kerinci Regency, Jambi. Depati Parbo Kerinci Airport is class III. The airport is 1,800 m long and 30 m wide. Currently, flights from Depati Parbo Airport are served by ATR 72 aircraft belonging to Wings Air. To date the largest aircraft ever in service is the ATR 72-600. The turn pad area is a place for a 180 degree turn, which is also useful if provided in several areas along the runway to reduce taxiing time and distance traveled by aircraft that do not require the entire runway. For now, Depati Parbo Kerinci Airport is currently working on developing an airport covering an area of ​​4 hectares. In order to comply with the regulations, a turnpad area will be created at the end of runway 30 so that turning aircraft can rotate on the turnpad and not perform one wheel lock on the runway which can damage the runway pavement. The pavement thickness planning method used is the International Civil Aviation Organization (ICAO) and the Federal Aviation Administration The pavement thickness method used is the International Civil Aviation Organization (ICAO) and the Federal Aviation Administration (FAA) which is carried out by manual calculations (AC 150-5320 6D) and FAARFIELD software (AC 150-5320 6F), while to calculate PCN using COMFAA software (AC 150- 5335-5C). From the planning results using the FAARFIELD-COMFAA correction method, it is known that the total pavement thickness is 18.9 inches. This includes a 4 inch surface layer, a 6 inch Base Course layer, and an 8.9 inch subbase layer. The PCN value obtained is 13.2, the ACN value is 13 and the CDF is 0.9069. Calculation of RAB for the manufacture of turn Pad area of ​​Rp. Rp 277,857,000.00